Numerical Analysis of Castellated Steel Beams with Offset Reinforced Steel Rings Around Web Openings - Mohamed Alarabi Munir; Otman Bubaker Alhodiry (African Journal of Advanced Pure and Applied Sciences, 2025)
This study investigates the behavior of castellated steel beams with circular and hexagonal web openings reinforced by ring stiffeners offset from the opening edge. Two depth-to-opening ratios (D/H = 0.4 and 0.7) were examined. Stiffeners were placed at four offset distances (0, 5, 10, and 15 mm). Finite element models were developed using the finite element analysis program Abaqus/CAE and verified with published experimental data. The results show that increasing offset can raise the ultimate load, particularly for castellated beams with large hexagonal openings (D/H=0.7). A moderate offset distance of 10 mm provided the best performance, especially for beams with large hexagonal opening ratios (D/H=0.7). The ductility also improves with moderate offset distance.